The Influence of Human Resources Management Practices & Employees' Outcomes in the Organizational Performance of Small Businesses in Baghdad - Yusra Yaseen, Lazim; Noor Azlinna, Azizan (Universiti Malaysia Pahang, 2012)
Human resources best practices are functional activities and strategic plans that enable improved services to employees and increased profitability for the employer. Using data from Iraq, paper investigates the relationship among human resources management practices, the employees' outcomes, and the organizational performance in small businesses. This study derives from three fields of knowledge: human resources management, employee outcomes, and organizational performance. Questionnaires are distributed to 16 small businesses in Baghdad, Iraq and analyze by using Arithmetic mean, Standard deviation, Coefficient of variation, Spearman, Simple linear regression and Mann Whitney test. The finding suggests that there are significant relationships between a group of human resources management practices in small businesses, and commitment, trust, involvement, cooperation, while it did not record a clear relationship with the latter variable.